New age constraints on the MIS 9 – MIS 5.3 marine terraces of the Pontine Plain (central Italy) and implications for global sea levels. (15th January 2023) - Marra, F.; Sevink, J.; Tolomei, C.; Vannoli, P.; Florindo, F.; Jicha, B.R.; La Rosa, M.
Abstract: New constraints were set on the age of marine deposits in the Pontine Plain and of the related sea level indicators on the Tyrrhenian Sea coast of central Italy by twelve new 40 Ar/ 39 Ar dates on detrital sanidine from these deposits. By combining a new geomorphologic analysis and previous morpho-pedo-stratigraphic studies with these geochronological constraints we reconstructed the geometry of four marine terraces and correlated these with the highstands during the marine isotopic stages (MIS) 9.3, 7.5, 5.5 and 5.3. Results point to a progressive tilting of the terraces, the elevation increasing from the SE to the NW due to differential tectonic uplift that occurred over the last 300 ka. We identified a MIS 9 sea level at 30 - 25 m asl in the northwestern sector, whereas the MIS 7.5 sea level reached a maximum of 24 m asl in the NW and descended to 18 m asl in the central sector. Moderate tilting affected the MIS 5.5 sea level, with an elevation of 12 to 9.5 m asl in between the Anzio and Circeo headlands. Finally, an undeformed MIS 5.3 sea level at ca. 3 m asl is indicated throughout this coastal reach, confirming previous data suggesting a much higher absolute sea level during this highstand with respect to the δ 18 O-derived predicted level. Highlights: We provide 12 new 40 Ar/ 39 Ar dates on a suite of marine terraces in the Pontine Plain. We correlate these terraces with marine isotopic stages (MIS) 9.3, 7.5, 5.5 and 5.3 We identify sea-level indicators for each one of these isotopic stages. The MIS 5.5 sea level occurs at 12 to 9.5 an asl as a consequence of tectonic tilting. We show that the MIS 5.3 sea level occurs at 2–3 m asl throughout this coastal reach.